Differences between laparoscopic super-radical hysterectomy and laterally extended endopelvic resection - Hiroyuki Kanao; Tomoko Kurita; Yuji Tanaka; Atsushi Fusegi; Yoichi Aoki; Hidetaka Nomura (Elsevier, 2021)
In 2003, Höckel described the laterally extended endopelvic resection (LEER), which may be an effective surgical technique for patients with laterally recurrent cervical cancer (Höckel, 2003). Super-radical hysterectomy, which was introduced by Ryukichi Mibayashi in 1941, is the traditional surgical approach for cervical cancer patients (Kim et al., 2017). These two procedures are similar and belong to the same group (type D) in the Querleu-Morrow classification (Querleu et al., 2017). Until now, no surgical video clearly demonstrated their differences, because technical complexities and concern for procedural safety are still being debated.The present video demonstrated total pelvic exenteration (TPE) for laterally recurrent, previously irradiated cervical cancer that involved both the bladder and rectum. In this case, the recurrent tumor infiltrated the parametrium, reached the left pelvic sidewall, and invaded the left piriform muscle, sacrospinous ligament, and spine segment S2. To completely clear the tumor, we used TPE with super-radical hysterectomy on the right side and LEER on the left. We performed this procedure laparoscopically because improved visualization allows for meticulous dissection and a higher possibility of achieving R0.Surgery time was 9 h 45 min including the time for creation of the ileal conduit and colostomy, and blood loss was 230 ml with no blood transfusion needed. Pathological R0 resection was achieved without any intraoperative and postoperative complications. Compared to super-radical hysterectomy, LEER ensured additional surgical margins.Without any adjuvant treatment, there has been no sign of recurrence during the 12 months that have passed since the surgery.Laparoscopic TPE with super-radical hysterectomy and LEER for laterally recurrent, previously irradiated cervical cancer is a technically feasible and safe surgical option. LEER can ensure more surgical margins than super-radical hysterectomy, and it may be a treatment of choice for more advanced lateral recurrence.